Dao during the Japanese occupation of Antique, 1942-1945. - Hualde, Melanie Escarira
This study of Dao during the era of Japanese colonialism in the Philippines, specifically, aims to describe the economic, political and socio-cultural conditions of Dao before and during the occupation, assess the effects of the occupation on the Daonhons, uncover various measures used by the Daonhons in dealing with Japanese militarism and identify the contribution of the local leaders of Dao to Antique's liberation. To be able to carry out the objectives, 45 respondents consisting of the local residents and World War II veterans were interviewed using two sets of guide questions - one for the local residents and the other fort the World War II veterans. Library research was also conducted to further supplement the data. The data was analyzed using frequency and percentage distribution., The three-year Japanese occupation of Antique indeed affected Dao in terms of economic, political and socio-cultural aspects. In dealing with enemies, Daonhons had adapted measures that prevented them rom further Japanese atrocity. It was also due to the courage and willingness of the local leaders such as guerillas, teachers and others that made Dao experience less cruelty from the Japanese. The local leaders and residents of the town also had significant participation in wartime activities that in a way contributed to the success of the struggle for the liberation of the Antiquenos.